Pengaruh Human Relation, Kompensasi Financial dan Kompetensi Terhadap Kinerja Karyawan - Nur Indah Permatasari; Hadi Sunaryo; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purpose of this study was to analyze and explain the influence of human relations, financial compensation and competence on employee performance at Bank BTN Syariah Malang. The dependent variable in this study is employee performance and there are 3 independent variables used, namely human relations, financial compensation and competence. The population in this study were employees of Bank BTN Syariah Malang. The sampling technique using saturated sampling technique obtained a sample of 60 respondents. The data collection method used is the distribution of questionnaires to respondents. The data analysis technique used is multiple linear regression. The results of this study indicate that simultaneously the variables of human relations, financial compensation and competence have a significant effect on employee performance. While partially human relations have a significant effect on employee performance, but financial compensation and competence have no significant effect on employee performance.  Keywords: Human Relations, Financial Compensation, Competence And Employee Performance.